Eosinopenia and increased markers of endothelial damage are characteristic of COVID-19 infection at time of hospital admission. (1st July 2022) - de Vries, Marouscha P.; Mohammadnia, Nieky; Simsek, Suat; Schoorl, Marianne
Abstract: In December 2019, a new virus has been discovered, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), leading to coronavirus disease 2019 (COVID-19). COVID-19 has been defined as an evolving disease with different phases. It starts with a mild or asymptomatic phase in which there is minimal disease. Thereafter, most patients recover, however, in 20% of the cases the infection worsens. It is hypothesized that eosinopenia, endothelial injury and the presence of smooth muscle autoantibodies are associated with the severity of the COVID-19. In a subset of 75 blood samples of patients with a SARS-CoV-2 infection at time of hospitalization and 30 healthy control samples concentrations of eosinophils, VEGF, VCAM, endothelin and smooth muscle autoantibodies were determined with hemocytometry, ELISA and immunofluorescence assays. In the group of patients with COVID-19 eosinophils (IQR = 0.0–0.01*10 9 /L) were significantly decreased ( p  < .001), whereas markers of endothelial damage VCAM (IQR = 740–1120 ng/mL) and endothelin (IQR = 2.0–3.4 pg/mL) were significantly increased ( p  < .001) compared to the group of healthy controls (eosinophils IQR = 0.09–0.19*10 9 /L, VCAM IQR = 362–561 ng/mL, endothelin IQR = 0.5–1.0 pg/mL). From the multivariate analysis, it is concluded that at time of hospitalization a combination of eosinopenia and increased markers of endothelial damage VCAM and endothelin are characteristic of COVID-19.